In vitro comparative quality assessment of different brands of hydrochlorothiazide tablets marketed in Northeast Ethiopia - Wondmkun, Yehualashet Teshome; Desta, Haile Kassahun; Ali, Yimer Seid; Tsige, Abate Wondesen; Ayenew, Kassahun Dires; Endalifer, Bedilu Linger; Dagnew, Samuel Berihun (Frontiers in Analytical Science, 2024)
Background: This study aimed to evaluate the quality and physicochemical bioequivalence of commercially available brands of hydrochlorothiazide tablets in community pharmacies in Dessie town, Northeast Ethiopia.Experimental-based cross-sectional study design was applied using pharmacopeia and non-pharmacopeia methods. Difference (f1) and similarity (f2) factor values were calculated to assess the in vitro bioequivalence of generic products with the comparator.The study revealed that all investigated brands contain the required active pharmaceutical ingredients. The friability test result was concordant with the United State Pharmacopeia (USP) (<1%) in eight brands, however, brand NF3 (1.36%) failed to pass specification limit. The hardness level of brand NF3 (24.20 N ± 7.32), NF5 (32.19 N ± 4.78), and NF9 (35.02 N ± 3.12) were below the specification limit hardness limit result was concordant (39.23Newton, USP 2019). All generic product weight variation results complied with the USP specification requirement. In the quantitative assay result, the minimum and maximum API (active pharmaceutical ingredient) content were 97.4±0.02 (NF6) and 105.8±0.02 (NF8), respectively API (active pharmaceutical ingredient) which is was within the limit of USP (90% up to 110%). Similarly, all samples meet the disintegration time limit (i.e., ≤ 30 minutes) and drug-releasing tolerance limit (API released more than 60% within 60 minutes). The f2 values were >50 & f1 values were ˂15 for all sampled brands.The majority of sampled brands of hydrochlorothiazide (HCT) tablets met the quality requirements as per USP official test specifications. From similarity factor and difference factor values, all studied brands were equivalent.